Numerical analysis of the wave propagation in a composite medium - Katauskis, P.; Skakauskas, V. (Mathematical Modelling and Analysis, 2006)
We consider the wave propagation process in a 2‐dimensional material structure composed of random oriented orthotropic crystals and analyse numerical results for the diffraction problem and the problem of waves interaction with a free boundary. First Published Online: 14 Oct 2010